Pancasila Sebagai Landasan Filosofis Pendidikan Nasional - I Putu Agus Aryatnaya Giri; Ni Luh Ardini; Ni Wayan Kertiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The foundation of philosophy in education is very important. The foundation of educational philosophy will direct humans or educators to think deeply or rooted about the nature of education. In addition, the existence of a nation is reflected in the educational philosophy adopted. Likewise, a good education reflects the foundation of a strong and solid educational philosophy. Education is said to be good, when it is able to produce ideal quality humans. The results of the analysis describe that the Indonesian nation has Pancasila as the country's philosophy. Pancasila should be the soul of the Indonesian nation, to be enthusiastic in working in all fields, especially education. The practice of Pancasila must be in the whole and integrity of the five precepts in the Pancasila, as formulated in the preamble to the 1945 Constitution, namely God Almighty, just and civilized humanity, Indonesian unity, democracy led by wisdom in deliberation / representation, and Social justice for all the people of Indonesia. For the education sector, this is very important because there will be certainty of values ​​that will guide the implementation of education.